98.7k views
1 vote
Help please

simplify the following using L'Hôpital's Rule:

\displaystyle\lim_(x\to 2)(x^2+x-6)/(x^2-4)

\text{note:explanation is a must}

2 Answers

5 votes

Answer:


\displaystyle \: (5)/(4)

Explanation:

we are given a expression

we are said to solve it using L'Hôpital's Rule

recall, L'Hôpital's Rule:


\displaystyle \lim _(x \to \: c)( (f(x))/(g(x)) ) = \lim _(x \to \: c) \frac{f ^(')(x) }{ {g}^(')(x) }

it is to say the ' means derivative

our given expression:


\displaystyle\lim_( x\to 2)(x^2+x-6)/(x^2-4)

let's apply L'Hôpital's Rule


\displaystyle\lim_( x\to 2)( (d)/(dx) (x^2+x-6))/( (d)/(dx) (x^2-4))

some formulas of derivative


\displaystyle \: (d)/(dx) {x}^(n) = {nx}^(n - 1)


\displaystyle \: (d)/(dx) {x}^{} = 1


\displaystyle \: (d)/(dx) {c}^{} = 0


\sf \displaystyle \: (d)/(dx) {f}^{} (x) + {g}^{}(x) = {f}^(') (x) + {g}^(')(x)

use sum derivative formula to simplify:


\displaystyle\lim_( x\to 2)( (d)/(dx) (x^2)+ (d)/(dx) (x) + (d)/(dx)( -6))/( (d)/(dx) (x^2) + (d)/(dx) (-4))

simplify using exponents using exponent derivative formula:


\displaystyle\lim_( x\to 2)( 2x+ (d)/(dx) (x) + (d)/(dx)( -6))/( 2x + (d)/(dx) (-4))

use variable derivative formula to simplify variable:


\displaystyle\lim_( x\to 2)( 2x+ 1+ (d)/(dx)( -6))/( 2x + (d)/(dx) (-4))

use constant derivative formula to simplify derivative:


\displaystyle\lim_( x\to 2)( 2x+ 1+ 0)/( 2x + 0)

simplify addition:


\displaystyle\lim_( x\to 2)( 2x+ 1)/( 2x )

since we are approaching x to 2

we can substitute 2 for x


\displaystyle\lim_( x\to 2)( 2.2+ 1)/( 2.2 )

simplify multiplication:


\displaystyle( 4+ 1)/( 4)

simplify addition:


\displaystyle \: (5)/(4)

hence,


\displaystyle\lim_( x\to 2)( (d)/(dx) (x^2+x-6))/( (d)/(dx) (x^2-4)) = (5)/(4)

User Chiffa
by
5.4k points
1 vote

Answer:

5/4 is your answer hope it helps

Help please simplify the following using L'Hôpital's Rule: \displaystyle\lim_(x\to-example-1
User Ancab
by
5.0k points